Influence of extremely low frequency electromagnetic field on antioxidant system and change of volatile composites in Pinus sylvestris L. - Esim, Nevzat; Kiliç, Ömer; Tiryaki, Deniz; Bengü, Aydın Şükrü (Progress in Nutrition, 2017)
The present study investigated the effect of extremely low frequency electromagnetic fields (ELF - EMFs) from high voltage power line on the antioxidant balance and inducible volatile emissions of Pinus sylvestris L. needles. The samples were collected from pines just below power line (P0, 50.66 mG) and 10 meter away from same power line. They were then categorized as P0 (just below power line) and 10 meter away from the same power line (P10, 6.30 mG). ELF - EMFs inhibited superoxide dismutase (SOD), catalase (CAT), and peroxidase (POX), but increased hydrogen peroxide (H2O2) and malondialdehyde (MDA) contents in needles of P0 plants. Therefore, volatile components of needles were investigated by GC-MS. The total rate of the volatile components for P0 and P10 plants was determined as 93.39% and 95.11%, respectively. α-pinene (20.74%), cyclohexene (9.20%), caryophyllene (9.10%) and bornylacetate (8.13%) were identified as main components in needles of P0 plants, and α-pinene (17.40%), bornylacetate (17.33%), cyclohexene (14.98%) and β-pinene (13.24%) in needles of P10 plants. Consequently, our findings suggest that Pine trees are sensitive to ELF - EMFs emitted from power line due to cause oxidative damage and alter the rate of volatile components in pine.